Survey of Community Sports Interest In Using Sports Facilities In Peruri Karawang Housing - Sabrina, Tasyaratu; Luthfia, Gariza; Mulyani, Sri; Setiawan, M. Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study explores the community's interest in utilizing sports facilities at Perumahan Peruri, Karawang. It aims to identify factors influencing the public's motivation to engage in physical activities. A survey method was employed, using structured questionnaires distributed to 20 randomly selected residents. The findings reveal a moderate interest level, with an average score of 71.3, ranging from 63 to 76. Key factors affecting interest include awareness of the importance of exercise, quality and accessibility of facilities, and the availability of leisure time. The results indicate that while community interest is relatively good, it remains suboptimal. To improve participation, strategic measures such as upgrading facility quality, promoting health awareness campaigns, and offering flexible exercise programs are recommended. This research provides a foundation for developing policies to encourage a more active and healthier community.